Long-Term Results of Neurological Outcome, Quality of Life, and Cosmetic Outcome After Cranioplastic Surgery: A Single Center Study of 202 Patients - Giese, Henrik; Antritter, Jennifer; Unterberg, Andreas; Beynon, Christopher (Frontiers in Neurology, 2021)
Objective: An increased interest in the surgical procedures of decompressive craniectomy (DC) and subsequent cranioplasty (CP) has emerged during the last decades with specific focus on mortality and complication rates. The aim of the present study was to evaluate long-term neurological and cosmetic outcomes as well as Quality of Life (QoL) after CP surgery. Methods: We retrospectively reviewed the medical records of CP patients treated at our institution between 2004 and 2014 and performed a follow-up examination, with evaluation of neurological outcome using the modified Rankin Scale (mRS) and the Glasgow outcome scale (GOS), QoL (SF-36 and EQ-5D-3L). Furthermore, the cosmetic results after CP were analyzed. Results: A total of 202 CP-patients were included in the present study. The main indications for DC and subsequent CP were space-occupying cerebral ischemia (32%), traumatic brain injury (TBI, 26%), intracerebral or subarachnoid hemorrhage (32%) and infection (10%). During a mean follow-up period of 91.9 months 46% / 42.6% of patients had a favorable neurological outcome (mRS ≤3 / GOS ≥4). Patients with ischemia had a significant worse outcome (mRS 4.3±1.5) compared with patients after TBI (3.1±2.3) and infectious diseases requiring CP (2.4±2.3). The QoL analysis showed that less than one third of patients (31.2%) had a good QoL (SF-36) with a mean EQ-5D-VAS of 59±26. Statistical analysis confirmed a significant worse QoL of ischemia patients compared to other groups whereas multivariate regression analysis showed no other factors which may had an impact on the QoL. The majority (86.5%) of patients were satisfied with the cosmetic result after CP and regression analysis showed no significant factors associated with unfavorable outcomes. Conclusion: Long-term outcome and QoL after CP were significantly influenced by the medical condition requiring DC. Early detection and evaluation of QoL after CP may improve the patient’s outcome due to an immediate initiation of targeted therapies (e.g. occupational- or physiotherapy).